An In‐Situ Self‐regeneration Catalyst for the Production of Renewable Penta‐1, 3‐diene. Issue 37 (19th May 2021) - Feng, Ruilin; Qi, Yanlong; Liu, Shijun; Cui, Long; Dai, Quanquan; Bai, Chenxi
Abstract: Catalyst deactivation is a problem of great concern for many heterogeneous reactions. Here, an urchin‐like LaPO4 catalyst was easily developed for pentane‐2, 3‐diol dehydration; it has an impressive ability to restore the activity in situ by itself during the reaction, accounting for its high stability. This facilitates the efficient production of renewable penta‐1, 3‐diene from pentane‐2, 3‐dione via a novel approach, where penta‐2, 3‐diol was obtained as an intermediate in 95 % yield under mild conditions. Abstract : An alternative approach to the efficient production of penta‐1, 3‐diene: Bio‐based hydrogenation of pentane‐2, 3‐dione by a Pt/Ce/Al2 O3 catalyst under mild conditions with a selectivity of 97 %, followed by dehydration by an urchin‐like LaPO4 catalyst afforded penta‐1, 3‐diene in yield of 59 %. The LaPO4 self‐regenerated during the dehydration owing to its ability to restore the active sites in situ.